Genomic delineation and description of species and within-species lineages in the genus Pantoea - Crosby, Katherine C.; Rojas, Mariah; Sharma, Parul; Johnson, Marcela A.; Mazloom, Reza; Kvitko, Brian H.; Smits, Theo H. M.; Venter, Stephanus N.; Coutinho, Teresa A.; Heath, Lenwood S.; Palmer, Marike; Vinatzer, Boris A. (Frontiers in Microbiology, 2023)
As the name of the genus Pantoea ("of all sorts and sources") suggests, this genus includes bacteria with a wide range of provenances, including plants, animals, soils, components of the water cycle, and humans. Some members of the genus are pathogenic to plants, some are suspected to be opportunistic human pathogens, while others are used as microbial pesticides or show promise in biotechnological applications. During its taxonomic history, the genus and its species have seen many revisions. However, evolutionary and comparative genomics studies have started to provide a solid foundation for a more stable taxonomy. To move further towards this goal, we have built a 2509-gene core genome tree of 437 public genome sequences representing the currently known diversity of the genus Pantoea. Clades were evaluated for being evolutionarily and ecologically significant by determining bootstrap support, gene content differences, and recent recombination events. These results were then integrated with genome metadata, published literature, descriptions of named species with standing in nomenclature, and circumscriptions of yet-unnamed species clusters, fifteen of which we assigned names under the nascent SeqCode. Finally, genome-based circumscriptions and descriptions of each species and each significant genetic lineage within species were uploaded to the LINbase Web server so that newly sequenced genomes of isolates belonging to any of these groups can be precisely and accurately identified.